Giardia duodenalis in Alpine (Rupicapra rupicapra rupicapra) and Apennine (Rupicapra pyrenaica ornata) chamois. Issue 1 (December 2015) - De Liberato, Claudio; Berrilli, Federica; Marangi, Marianna; Santoro, Maristella; Trogu, Tiziana; Putignani, Lorenza; Lanfranchi, Paolo; Ferretti, Francesco; D'Amelio, Stefano; Giangaspero, Annunziata
Abstract Background Although chamoisRupicapra spp. are the most abundant mountain ungulates in Europe, no data are available on the presence ofGiardia duodenalis infecting these species. Methods A total of 157 fecal samples from AlpineRupicapra rupicapra rupicapra and ApennineRupicapra pyrenaica ornata chamois were tested for the presence ofG. duodenalis by immunofluorescence test, quantitative Real Time PCR and end-point PCR for genotype characterization. Results G. duodenalis was detected inR. r. rupicapra andR. p. ornata, with a percentage value of 4.45 (5.82 and 1.85 %, respectively), and a cyst burden of up to 31, 800 cysts/g of feces. Assemblages A/AI and E were identified inR. r. rupicapra and assemblage A/AIII inR. p. ornata . Conclusions The present study represents the first record ofGiardia duodenalis inRupicapra spp., suggesting that these wild bovids can play an epidemiological role in environmental contamination and transmission of both zoonotic and non-zoonotic genotypes.